Authentic Christianity ; v. 3 sermons on the Acts of the Apostles - Lloyd-Jones, David Martyn, 1899-1981 (Edinburgh, Scotland Banner of Truth Trust, 2003)
Contents : v. 3 : Acts 5 and 6
Keywords: Bible. N.T. Acts -- commentaries; Bible. N.T. Acts -- addresses, sermons, lectures